EFL teachers perceived productive skills for effective teacher professional development program - Yenni Rozimela; Sitti Fatimah; Aryuliva Adnan; Sintha Tresnadewi (Universitas Syiah Kuala, 2024)
Indonesian EFL teachers English competency has been in the spotlight due to their unsatisfactory achievement. This reality has been observed during their practices in the classroom. This article aims at reporting the results of Indonesian EFL teachers perception of their productive English skills, speaking and writing. A mixed method was employed by focusing on introspective method. Quantitative data were obtained through a closed-ended questionnaire filled in by 206 secondary school teachers and analysed using SPSS software. Ten randomly selected teachers were interviewed to confirm the quantitative data. The findings show that EFL teachers speaking and writing skills are at a moderate level (68.62-71.70) and (67.83-71.18), respectively. Interview results indicate a low intensity of spoken English use in the classroom, which is less than 50%. This occurred for two main reasons: the students low ability to understand teachers talk/explanation and the teachers declining speaking ability. Meanwhile, only 2 of 10 teachers taught writing by following the steps of the writing process. However, at the interview session, the teachers rated themselves for speaking from 6-9 and for writing from 5-9. All teachers agreed that training to improve their English proficiency was highly important; this could be realised through the MGMP program. The results of these data will be used to develop a prototype of the Competency Test for Indonesian English Teachers (CTIET) to develop EFL teachers sustainable English proficiency.